Decoupling and Recoupling - Korinek, Anton; Roitman, Agustín; Végh, Carlos A (American Economic Review, 2010)
We develop a stylized model that captures the phenomena of decoupling and in an environment where heterogeneous entrepreneurial sectors face financial constraints in their relationship with a common set of lenders. In response to adverse shocks, a financially constrained sector must reduce its borrowing and cut down on production. In particular, as the constrained sector absorbs less and less capital, the real interest rate in the economy declines. Other sectors that compete for the same inputs (including capital) thus experience lower costs, which boosts investment, output, and profits, reflecting the phenomenon of decoupling. As long as the shock is small, the entrepreneurial sector repays what is owed and the lenders' ability to supply funds is unaffected. For large shocks, however, the constrained sector is no longer able to honor its debts in full and lenders experience losses that erode their lending base. This induces them to cut their supply of credit to the rest of the economy, which reduces output and profit for all other entrepreneurial sectors, capturing the phenomenon of recoupling or contagion.